Dementia and family burden of care in Lebanon. (2nd January 2018) - Chaaya, Monique; Phung, Kieu; Atweh, Samir; El Asmar, Khalil; Karam, Georges; Khoury, Rosemary; Ghandour, Lilian; Ghusn, Husam; Assaad, Sarah; Prince, Martin; Waldemar, Gunhild
Abstract : The burden on and mental well-being of family carers for the elderly, especially those with dementia, has been well studied in high-income countries and to a lesser extent in the Arab region. Our study of Lebanese carers highlights the importance of considering the psychological well-being of the family carer, and the role of dementia and depression in increasing the burden of care. Psychosocial interventions have produced equivocal results and therefore customised and contextualised interventions need to be researched. Greater understanding of the coping mechanisms used by carers is required and an examination of the positive aspects of caring is warranted.